Analisis Pengaruh Lingkungan Keluarga terhadap Hasil Belajar Siswa pada Pelajaran Fiqih di MTs Al-Khairaat Gorontalo - Muhammad Nur Iman Iman; Saifulhaq Inaku Saiful; Suheil Suheil (Kariman: Jurnal Pendidikan dan Keislaman, 2020)
This study aims to determine the extent of the influence of the family environment on student learning outcomes in fiqh lessons at Mts Al-Khairaat Gorontalo. The research is quantitative with a population of 150 students, and strengthened by primary and secondary data sources, which are then analyzed using certain analytical instruments, while the results of the study show that the family environment is one of the factors that have an influence on student learning outcomes. The influence of the contribution of 35.4% to the student learning outcomes variable, while the other 64.6% is influenced by other factors outside the variables studied. So the findings of this study are in accordance with the mindset put forward in the conceptual framework in which a good family environment tends to have a positive effect, so that children's learning outcomes are good. Conversely, if the family environment is not good, a large trend will have a negative impact on student development.